NATURAL FEED (ROTIFER) MANAGEMENT ON ORANGE SPOTTED GROUPER Epinephelus coioides LARVAL REARING - Titiek Aslianti; Irwan Setyadi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
ABSTRACT According to Indonesian Standard Quality, the optimal seed production of orange spotted grouper (Epinephelus coioides) has been unsuccessful due to the problems occurred during larval rearing period. Efforts on mass rearing of larvae has been carried out in this study to optimize the natural feeding (rotifer). The purpose of this research was to obtain the information about an appropriate duration time for natural feeding (rotifer) to produce higher survival rate. The treatment for providing rotifers on larvae (days after hatching/DAH) i.e., (A) 20 days, (B) 25 days, (C) 30 days, and (D) 35 days. Rotifers were enriched with DHA Selco. Experiment used fiber tanks with 1 m3 capacity with a completely randomized design (CRD) and three replicates. The larvae was reared to achieve the juvenile phase (D-45). The best results from 1 m3 tanks were then reared using concrete tanks of 6 m3 and 10 m3 capacities. The results showed that feeding of rotifers up to 25 DAH larvae on fiber tanks (1 m3) produced the hughest survival rate (7.63 %). Meanwhile, the mass reared in 6 m3 and 10 m3 concrete tanks produced  survival rate of 4.9±3,54% and 8.8±2.26%, respectively. The homogenous size was relatively high (80%) and the seed abnormality was relatively low (0.4%).   Keywords: rotifers, feeding time, Orange Spotted  grouper larvae, Epinephelus coioides